Libraries for research excellence: research support service through subject liaison librarians - Wijesundara, Chiranthi; Silva, M.A.L.; Somaratna, Sajeewanie D. (University of Colombo, 2023)
University libraries adopt diverse methods to enhance the research productivity of their patrons, and research support is one such vital service among them. The library of the University of Colombo has continuously provided research support for students in numerous ways over the decades; however, awareness of these services was limited. Therefore, the research support services were restructured, customized with the subject liaison librarians, and promoted among the students via social media, academic and student groups. The service is delivered by the subject liaison librarians of the library at the University of Colombo, who are specialized in diverse subject domains. This research overviews the status of the current research support service as a preliminary survey for the patrons’ benefit in the future. A survey research design was used for the study. A census was conducted by administering a structured questionnaire as a Google form. The authors collected 128 student requests from February to August 2023. The obtained data were analyzed with descriptive statistics and the Pearson Chi-Square Test, and significance was determined at a 5% level. Out of 128 total requests, 83.59% (n=107) were made by undergraduates following the special degree, while general degree students made 16.41% (n=21). The majority (58.59%, n=21) of the research support requests were made by the undergraduates of the Faculty of Arts, whereas the Faculty of Law made the least (10.16%, n=13) requests. When analyzed by degree program, the highest number of requests (16.41%, n=21) were made by the Business Administration (Honours) students of the Faculty of Management. There were seven categories related to research support, and the requests for writing an assignment/ report and selecting reading materials were the highest requested areas, while the writing an abstract/ proposal was the least requested. The Chi-Square test proved a significant relationship amongst the faculties for the research support services on writing an abstract/ proposal (p=0.0213). In contrast, other research support services did not reveal any significant relationship among the faculties. The undergraduates following the general degree expected more general skills, for instance, information retrieval, while the honours degree students required more subject-specific research support related to their final year dissertation topics, highlighting the importance and expertise of the subject liaison librarians. The study emphasizes that the involvement of librarians with multidisciplinary subject knowledge is essential to provide a better service through research support for the undergraduates of the university.
Keywords: library; research support; subject liaison librarians; undergraduates; Sri Lanka